Efficacy and immunogenicity of a single dose of human papillomavirus vaccine compared to multidose vaccination regimens or no vaccination: An updated systematic review of evidence from clinical trials - Hilary S. Whitworth; Sandra Mounier-Jack; Edward M. Choi; Katherine E. Gallagher; Natasha Howard; Helen Kelly; Gladys Mbwanji; Aimée R Kreimer; Partha Basu; Ruanne Barnabas; Mélanie Drolet; Marc Brisson; et al. (Vaccine: X, 2024)
Objectives: This study systematically reviewed the published literature from clinical trials on the efficacy and immunogenicity of single-dose HPV vaccination compared to multidose schedules or no HPV vaccination. Methods: Four databases were searched for relevant articles published from Jan-1999 to Feb-2023. Articles were assessed for eligibility for inclusion using pre-defined criteria. Relevant data were extracted from eligible articles and a descriptive quality assessment was performed for each study. A narrative data synthesis was conducted, examining HPV infection, other clinical outcomes and immunogenicity responses by dose schedule. Results: Fifteen articles reporting data from six studies (all in healthy young females) were included. One article was included from each of three studies that prospectively randomised participants to receive a single HPV vaccine dose versus one or more comparator schedule(s). The other 12 articles reported data from three studies that randomised participants to receive multidose HPV vaccine (or control vaccine) schedules; in those studies, some participants failed to complete their allocated schedule, and evaluations were conducted to compare participants who actually received one, two or three doses. Across all efficacy studies, the incidence or prevalence of HPV16/18 infection was very low among HPV-vaccinated participants, regardless of the number of doses received; with no evidence for a difference between dose groups. In immunogenicity studies, HPV16/18 antibody seropositivity rates were high among all HPV-vaccinated participants. Antibody levels were significantly lower with one dose compared to two or three doses, but levels with one dose were stable and sustained to 11 years post-vaccination. Conclusions: Results from this review support recent World Health Organization recommendations allowing either one- or two-dose HPV vaccination in healthy young females. Longer-term efficacy and immunogenicity data from ongoing studies are awaited. Randomised trials of single-dose HPV-vaccination are urgently needed in other populations, e.g. boys, older females and people with HIV.